2020
DOI: 10.1093/mnras/staa3926
|View full text |Cite
|
Sign up to set email alerts
|

Improving sampling and calibration of GRBs as distance indicators

Abstract: We present a sample of 74 Gamma-Ray Bursts (GRBs) from the Fermi-GBM catalogue for which we compute the distance moduli and use them to constrain effective dark energy models. To overcome the circularity problem affecting GRBs as distance indicators, we calibrate the Amati relation of our sample with a cosmology-independent technique. Specifically, we use the latest observational Hubble parameter data, including associated systematics, to approximate the cosmic expansion through a Bezier parametric curve. We s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 66 publications
2
24
0
Order By: Relevance
“…Calibrating the above correlations permits us to use GRBs as distance indicators (Wang & Wang 2019;Montiel et al 2020;Wei & Melia 2020). Clearly, we cannot consider GRBs as standard candles, although we aim to alleviate the circularity problem by adopting model-independent calibrations by means of data set that is independent enough of H(z), for which the luminosity distance d L is not computed by assuming an a priori cosmological model.…”
Section: Calibration Of Grb Correlationsmentioning
confidence: 99%
“…Calibrating the above correlations permits us to use GRBs as distance indicators (Wang & Wang 2019;Montiel et al 2020;Wei & Melia 2020). Clearly, we cannot consider GRBs as standard candles, although we aim to alleviate the circularity problem by adopting model-independent calibrations by means of data set that is independent enough of H(z), for which the luminosity distance d L is not computed by assuming an a priori cosmological model.…”
Section: Calibration Of Grb Correlationsmentioning
confidence: 99%
“…These GRB luminosity indicators have been widely used as standard candles for cosmology research (Schaefer 2007;Wang et al 2007;Amati et al 2008;Amati & Della Valle 2013;Wei et al 2013;Wang et al 2017;Amati et al 2019;Muccino et al 2021;Montiel et al 2021), and it has been shown that when combined with other probes, GRBs can indeed extend the Hubble diagram to higher redshifts and help to make better constraints on cosmological parameters (Amati & Della Valle 2013;Wang et al 2015, for a review). However, since the observed GRB rate falls off rapidly at low redshifts, it is very difficult to make a robust calibration for those GRB correlations.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [221], the E p -E iso correlation, calibrated with the latest OHD data set, has been jointly fit with CMB, BAO, and SNe Ia data in a search for cosmological parameter constraints within the standard cosmological model, as well as in dynamical dark energy parametrizations, finding no evidence in favor of the alternatives to the ΛCDM model. Finally, by using the Combo correlation with 174 GRBs calibrated in a semi-model independent way, in Ref.…”
Section: Numerical Results Using Correlationsmentioning
confidence: 99%
“…Inferred from the interpolation of the OHD data by using Bézier polynomials. b Inferred from the interpolation of the OHD data with additional systematic errors[221] by using Bézier polynomials. c Value from Ref.…”
mentioning
confidence: 99%